Модели ценовой политики на различных стадиях развития турпродукта - Швец, И.Ю. (Кримський науковий центр НАН України і МОН України, 2005)
In article presented deferent level of development a touristy severs, to presented Models of prices politic on deferent level of development a touristy severs. Keywords: level life cycle, prices politic, touristy severs.